Philosophy of physics - Butterfield, Jeremy; Earman, John.; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier/North-Holland, 2007)
The ambition of this volume is twofold: to provide a comprehensive overview of the field and to serve as an indispensable reference work for anyone who wants to work in it. For example, any philosopher who hopes to make a contribution to the topic of the classical-quantum correspondence will have to begin by consulting Klaas Landsmans chapter. The organization of this volume, as well as the choice of topics, is based on the conviction that the important problems in the philosophy of physics arise from studying the foundations of the fundamental theories of physics. It follows that there is no sharp line to be drawn between philosophy of physics and physics itself. Some of the best work in the philosophy of physics is being done by physicists, as witnessed by the fact that several of the contributors to the volume are theoretical physicists: viz., Ellis, Emch, Harvey, Landsman, Rovelli, t Hooft, the last of whom is a Nobel laureate. Key features - Definitive discussions of the philosophical implications of modern physics - Masterly expositions of the fundamental theories of modern physics - Covers all three main pillars of modern physics: relativity theory, quantum theory, and thermal physics - Covers the new sciences grown from these theories: for example, cosmology from relativity theory; and quantum information and quantum computing, from quantum theory - Contains special Chapters that address crucial topics that arise in several different theories, such as symmetry and determinism - Written by very distinguished theoretical physicists, including a Nobel Laureate, as well as by philosophers - Definitive discussions of the philosophical implications of modern physics - Masterly expositions of the fundamental theories of modern physics - Covers all three main pillars of modern physics: relativity theory, quantum theory, and thermal physics - Covers the new sciences that have grown from these theories: for example, cosmology from relativity theory; and quantum information and quantum computing, from quantum theory - Contains special Chapters that address crucial topics that arise in several different theories, such as symmetry and determinism - Written by very distinguished theoretical physicists, including a Nobel Laureate, as well as by philosophers.
General Preface (Dov Gabbay, Paul Thagard and John Woods) -- Introduction (Jeremy Butterfield and John Earman) -- List of Contributors -- On Symplectic Reduction in Classical Mechanics (Jeremy Butterfield) -- The Representation of Time and Change in Mechanics (Gordon Belot) -- Classical Relativity Theory (David Malament) -- Non-Relativisitic Quantum Theory (Michael Dickson) -- Between Classical and Quantum (N.P. Landsman) -- Quantum Information and Computing (Jeffrey Bub) -- The Conceptual Basis of Quantum Field Theory (Gerard 't Hooft) -- Algebraic Quantum Field Theory (Hans Halvorson) -- Issues in the Foundations of Classical Statistical Physics (Jos Uffink) -- Quantum Statistical Physics (Gerard Emch) -- Issues in the Philosophy of Cosmology (George F.R. Ellis) -- Quantum Gravity (Carlo Rovelli) -- Symmetrics and Invariances in Classical Physics (Katherine Brading and Elena Castellani) -- Aspects of Determinism in Modern Physics (John Earman) -- Index.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Physics -- Philosophy; SCIENCE -- Energy; SCIENCE -- Mechanics -- General; SCIENCE -- Physics -- General; Physics -- Philosophy; Natuurkunde; Filosofie; Electronic books